Written-response interview protocols: an innovative approach to confidential reporting and victim interviewing in sexual assault investigations - Heydon, Georgina (Policing and society, 2018)
The confidential reporting of sexual assaults can play an important role in support processes for victim-survivors and has the potential to improve the rate of official reporting of sexual assault to police. However, the self-reporting forms currently used for this purpose are not developed in line with the research evidence regarding forensic interviewing techniques, and nor have they been trialled and evaluated for their effective use in sexual assault investigations. This situation leads to substantial inconsistencies between the information gathering practices used by police in formal interviews, and the information gathering practices used in confidential, self-reporting contexts. In this article, we engage in a conceptual and critical consideration of current forms used in response to sexual assault. Ultimately, we propose that a written-response interview protocol (WRIP), has potential to improve the completeness and accuracy of evidence, as well as the consistency and experiences of victim-survivors of sexual assault.